Cara Wirausaha Muda Menghadapi Tantangan di Era Digital - Ebenezer Gulo; Denisman Laia; Yosia Bello (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Rapid developments in the digital era offer vast opportunities for young entrepreneurs, while also bringing complex challenges. Technological advances have opened up opportunities for wider access to information and markets. However, the challenges of fierce competition and changing technological dynamics are the main obstacles that need to be overcome. Young entrepreneurs must have the ability to adapt to the latest technological developments, such as digital marketing and artificial intelligence, while understanding how consumption patterns are changing with greater emphasis on convenience and personalization. However, overcoming dependence on digital platforms and resource limitations need to be overcome. In overcoming this situation, young entrepreneurs need to use technology to increase efficiency, be creative in creating new products and services, as well as expand networks and collaborate strategically. By managing finances wisely and being able to adapt to changes, it is hoped that young entrepreneurs can continue to exist and grow, and achieve success in an ever-changing global market, Young entrepreneurs in the digital age face big challenges along with advances in technology and changes in consumer behavior. However, with the right strategy, these obstacles can be turned into opportunities for growth and success. Utilizing technology, product innovation and digital marketing can increase efficiency, reach a wider market and increase profits. The ability to overcome digital challenges well opens up opportunities for young entrepreneurs to dominate the market, improve business reputation and achieve long-term growth. Adapting to change quickly will increase competitiveness and support sustainable growth.